Pengelolaan Pesisir melalui Penanaman Mangrove untuk Mendukung Pembangunan Berbasis Blue carbon di Kota Sorong - Abu, Nur; Dwangga, Mierta; Sumendar, Rian; Ibal, La (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The high potential for carbon content in mangrove tree species proves that the ecological benefits of the mangrove ecosystem have a positive impact on efforts to mitigate climate change and global warming. The aim of this service is to increase public understanding of the importance of mangrove planting in supporting blue carbon-based development in Sorong City. Involvement in this activity includes community, local, student, and academic participation. The method used is descriptive-qualitative in the form of socialization and mangrove planting actions. The result of this service is that it can provide an understanding that the existence of the mangrove ecosystem in the coastal area of Klawulu Village has an important role in providing protection to this area. This function also contributes as a mitigation measure against the risk of flooding and global warming. Apart from that, during community service activities, there was a change in understanding about mangroves, which then created a positive response from the community to participate in maintaining and protecting the mangrove ecosystem to prevent climate change.